Evolutionary dynamics of mimetic rings in heterogeneous ecological communities - Barros, Irina Birskis (2017)
Müllerian mimicry theory postulate that individuals of different species benefit from decreased per-capita attack risks by sharing similar warning signals. In species-rich mimetic assemblages, there is the formation of several distinct sympatric groups of species sharing the same warning signals, often color pattern, called mimetic rings. The coexistence of multiple rings seems paradoxical considering that selection among unpalatable species should favor convergence and thus reinforce a single color pattern. Different rings evolving in distinct habitats could explain the coexistence of multiple mimicry rings. However, the way species use the habitats might influence the emergence of multiple mimicry rings. We combined mathematical modeling and numerical simulations to explore how habitat heterogeneity, abiotic selection and habitat generalist species influence the formation of mimicry rings in a community. We showed that distinct selection pressures, derived from habitat heterogeneity, favored the formation of distinctive mimicry rings. Nevertheless, just the co-existence of species was enough to drive the emergence of the rings. Simulations in which there was just biotic or abiotic selection, time for convergence was faster than when both sources of selection acted together, suggesting conflicting selective pressures exerted by environment and co-existing species. In the presence of species that was habitat generalist, species converged to similar trait values, decreasing the distinctiveness of mimicry rings. A unique mimicry ring was formed if the different habitats optima in the community were very similar or when most species were habitat generalists. Our results suggest that multiple sympatric mimicry rings are formed by a complex interplay between abiotic and biotic selection and is only possible in groups of animals in which local species composition is strongly affected by habitat heterogeneity such as butterflies